Pendampingan pengembangan keterampilan guru Sekolah Dasar dalam soal evaluasi pembelajaran dengan Teka-teki Silang berbasis smartphone - Usman Sutisna; Mia Fitriah Elkarimah (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
The industrial 4.0 era requires an educator to increase competence or expertise in the use of information technology in education. The use of technology in education is extensive, including learning media and learning evaluation media. This goal is to develop the skills of SD Menteng Atas 01 teachers, especially in the IT field, and the ultimate goal of this community service activity is to encourage teachers to share learning media, especially smartphone media, in order to make learning evaluations. In the form of online crossword puzzles, especially during the pandemic, teaching and learning activities are now being carried out boldly. The service partners are all teachers at Menteng Atas Elementary School. Community service was held on April 13, 2020, at SDN Menteng Atas 01, followed by 15 participants online via zoom. The method used is demonstration and lecture. As a result of this community service activity, the teachers of SDN Menteng Atas 01 Setiabudi, South Jakarta, were able to create online crossword puzzles independently with a smartphone.